Treatment of urinary incontinence in a cat with genitourinary dysplasia using an urethral sphincter occluder. (21st July 2020) - Fournet, A.; Maurey, C.; Decambron, A.; Viateau, V.; Manassero, M.
Abstract : A 2‐year‐old spayed female Maine Coon presented with urinary incontinence and recurrent urinary tract infection since 2 months of age. Clinical examination was unremarkable. Ultrasonography, CT and cystourethroscopy revealed urogenital abnormalities consistent with genitourinary dysplasia. Urethral pressure profilometry suggested urethral sphincter mechanism incompetence. Surgical placement of an artificial urethral sphincter occluder was performed. Mild decrease of urinary incontinence was observed 6 weeks postoperatively. Inflation of the occluder under urethral pressure profilometry was subsequently performed and resolved the incontinence. This is the first report to describe the use of urodynamic testing at the time of inflation of an artificial urethral sphincter occluder to adjust the degree of urethral occlusion.